Analysis of Learning-based Material Android app Vector Loaded Authentic Learning Using TBLA Method (Transcript Based Lesson Analysis) - Aprilia Kharimatul Afifa; Mustika Wati; Mazlena Binti Murshed (Berkala Ilmiah Pendidikan Fisika, 2023)
Learning analysis needs to be done after the learning process ends to get reflections on previous learning. However, the results of the interviews obtained information from class X students that learning analysis had never been carried out. Therefore, analyzing the learning based on the Android application of vector material containing authentic learning through TBLA is necessary. The purpose of the research is to analyze the involvement of students and the use of keywords during the learning process using the Android application on vector material through TBLA. This research is a descriptive study. The subjects were 32 class X IPA 4 students and one physics teacher. The stages of data collection are plan, do, and see. The study results showed that the learning carried out during the first cycle was still teacher-centered. Cycle 1 learning takes place interactively. The use of the keyword during the first learning meeting was most pronounced, namely "vector" 23 times. Meanwhile, during cycle 2, it was also teacher-centered. The keyword most pronounced in the second cycle, namely "tight" was pronounced 43 times. The learning carried out is still teacher-centered, so based on the results of this analysis, it is recommended that further learning be more student-centered.